Mass transfer performance of curve blade impeller in gas-liquid mixing - Abdul Raman, Abdul Aziz; Nik Meriam, N.S.; Ibrahim, Shaliza (Non-ISI/Non-SCOPUS Cited Publication, 2004)
In this work the volumetric mass transfer coefficient, k a of a six bladed curve blade impeller 6CB was compared with a standard six bladed Rushton Turbine (6RT) by measuring dissolved oxygen content in 20cm diameter cylindrical tank. It was found that for gas rated in between 15liter/min and rpm in between 300 to 700rpm, 6CB gives 30-50% higher volumetric mass transfer compared 6RT at the same gas rate and impeller rational speed. For the same range of gas rates and impeller speed, volumetric mass transfer coefficient per unit power input for 6CB was found to be higher than 6RT by 61% to 130% hence making 6CB as a perfect candidate for retrofitting 6RT in order to obtain better mass transfer performance for liquid-gas system without changing motor and shaft assembly.